ANALISIS GAYA BAHASA (MAJAS) DAN MAKNA PADA CERPEN “TOMBAK SANG PENENUN“ KARYA BENNY ARNAS (KAJIAN STILISTIKA) - Fadhilah, Umu (GHANCARAN: Jurnal Pendidikan Bahasa dan Sastra Indonesia, 2020)
This research problem was about language style and figure of speech in a short story and analyze about short story meaning of " Tombak sang Penenun by Benny Arnas based on stylists study . Purpose of this research was knowing use language figure of speech and types figure of speech that was in the novel. This research use stylists approach .This Research data used descriptive data in the form phrases, words, and sentence based on short story of " Tombak sang Penenun by Benny Arnas . The results of the study found that research prove existence there is three type group figure of speech contained in short story that is group figure of speech comparison that includes personification , metaphor , and antonomasiai while group figure of speech affirmation there isn’t in this short story.